IMU Application in Measurement of Vehicle Position and Orientation for Controlling a Pan-Tilt Mechanism - Hendri Maja Saputra; Zainal Abidin; Estiko Rijanto (National Research and Innovation Agency, 2013)
This paper describes a modeling and designing of inertial sensor using Inertial Measurement Unit (IMU) to measure the position and orientation of a vehicle motion. Sensor modeling is used to derive the vehicle attitude models where the sensor is attached while the sensor design is used to obtain the data as the input to control the angles of a pan-tilt mechanism with 2 degrees of freedom. Inertial sensor Phidget Spatial 3/3/3, which is a combination of 3-axis gyroscope, 3-axis accelerometer and 3-axis magnetometer, is used as the research object. Software for reading the sensor was made by using Matlab™. The result shows that the software can be applied to the sensor in the real-time reading process. The sensor readings should consider several things i.e. (a) sampling time should not be less than 32 ms and (b) deviation ratio between measurement noise (r) and process noise (q) for the parameters of Kalman filter is 1:5 (i.e. r = 0.08 and q = 0.4).